A 6-component paddle sensor to estimate kayaker`s performance: preliminary results - Nates, F. M.; Colloud, F. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to measure the paddle shaft-hand interaction while an athlete paddled a kayak ergometer. The paddle shaft was specifically equipped with two 6-component force sensors to measure the contact force between the athlete`s hands and the paddle shaft. In order to minimise the error of the data collected, this new instrumentation was specifically calibrated for this experience. Preliminary results suggested that this new instrumentation provided data of high interest to improve our knowledge of the propulsion and recovery phases while kayaking an ergometer. In the future, this innovative instrumentation could be used during on-water sessions.